Análisis productivo y financiero de la finca cafetalera la Sanora en el cantón Chinchipe provincia de Zamora Chinchipe, para realizar un plan que genere una mejor rentabilidad en las fincas del sector - Paccha Reinoso, Brayan Francisco (2016)
This work focuses on the production and financial analysis of the La Sanora in Canton Chinchipe province of Zamora Chinchipe, for a plan to generate higher returns on farm sector. The objectives in this research are: to identify the coffee farms SANORA industry dedicated to the production of organic coffee; analyze the productive and financial processes of the Sanora coffee farm as the most representative of the sector; present a proposal to improve the profitability of the coffee farm La Sanora; socialize the results obtained with small farmers in the area. In the methodological part applies a survey, where the number of farms for the production of coffee (5 farms) was obtained was applied, then information was obtained about the production process of each of the farmers, it was determined the number of land used in the production of coffee, the activities developed in the first three years and the amount of production of coffee having each of the farms and the variety of coffee cultivation. The results of the research farm can be seen that there are five farms for the production of coffee, investment per hectare is $ 3,185.00, coffee production per hectare in the Sanora farm is 25 quintals, this It means data is because the characteristics of the sector are able to produce 30 to 40 quintals per hectare and the main problem will not get to produce this amount is because it is traditionally grown. Among the shortcomings noted it has that farmers do not carry adequate records of expenses and income to see if they have a utility; the main varieties grown in the area are: Bourbon, Caturra, Salchimor, which are preferred by producers to be resistant to rust, ojo de gallo and its adaptation to the environment. It is concluded that the unit cost per quintal of coffee is $ 127.40 , also profitability of the farm is of 77.29 % , which means that the total assets of the estate are the 77.29 % own ; as to the solvency of the estate it is 5.97 % , indicating that for every dollar farm debt is short term have $ 5.97. To improve the profitability of farms is recommended to increase agro-ecological technique to reduce energy, resources and regulate investment in production; make Silvopastoral implementing sustainable management and agroforestry techniques, leading financial records of agricultural production MONTHLY BASIS of the activities undertaken to take timely corrective measures.